Early supplier integration in the US defense industry. Issue 1 (16th October 2018) - Cohee, Garrett Lane; Barrows, Jeff; Handfield, Rob
Abstract : Purpose: Each year, the US defense industry outsources nearly $400 bn of domestic goods and services through competitive bids. These procurement activities are quite often complex and specialized in nature because of a highly regulated federal acquisition contracting environment. Ongoing calls to improve supplier management and drive innovation in the defense industry offers an opportunity to adopt Early Supplier Integration (ESI) initiatives that have proven successful in the private sector. This paper identifies critical ESI activities and acquisition practices that the defense industry should adopt to ensure enhanced effectiveness in new product development. Design/methodology/approach: Leveraging a conceptual ESI model derived from the research, an in-depth case study of 12 product development projects from a major defense contractor was performed. In the context of project performance, critical ESI activities and moderating effects were assessed. Findings: Three key ESI activities have the greatest impact on aggregate project performance: system design involvement, design adjustment opportunities and design for manufacturability/assembly/testability involvement. Use of formal supplier agreements also significantly impacts project performance during the development phase. In addition, project complexity and product team maturity were identified as environment moderators; higher complexity projects tended to negatively moderate the impact of ESI upon performance, and higher team maturity levels tended to positively moderate the impact of ESI upon performance. Originality/value: The results provide a sound framework for empirical validation through future quantitative studies and defense industry analyses. In addition, insights and recommendations for interpretation and adaptation of federal acquisition regulations to allow increased utilization of ESI within the defense industry are substantiated.